Review Of Cerebral Microbleeds using FAZEKA Classification - Singh, Bhanupriya; Shinde, Ganesh; Pandey, Manasvini (Nepal Journal of Neuroscience, 2023)
Introduction: Cerebral microbleeds (CMBs), also known as cerebral microhemorrhages, are tiny hypointense foci discovered by susceptibility-weighted (SW) magnetic resonance imaging (MR). CMBs have been interpreted as asymptomatic lesions that may be identified by chance during a brain MRI. This study was done to understand the etiology and various imaging patterns of the cerebral microbleeds on MRI Materials & Methods: This study was done with a sample size of 325 patients who underwent MRI Brain and diagnosed with CMB at our hospital. Detailed supportive history was taken and data was analysed. Results: Present study shows strong correlation between CMB’s and white matter changes. CMBs in parietal lobe found to have correlation with cognitive dysfunction. Lacunar infract is the most common subtype associated with the CMB’s Conclusion: The markers of microangiopathy on MRI brain are CMBs and white matter changes. Correlation of lobar CMBs with periventricular white matter hyperintensities and deep, infratentorial CMBs with deep white matter hyperintensities were found.